The Oncogene Transcription Factor EB Regulates Vascular Functions - Doronzo, Gabriella; Astanina, Elena; Bussolino, Federico (Frontiers in Physiology, 2021)
Transcription factor EB (TFEB) represents an emerging player in vascular biology. It belongs to the bHLH-leucine zipper transcription factor microphthalmia family, which includes microphthalmia-associated transcription factor, transcription factor E3 and transcription factor EC, and is known to be deregulated in cancer. The canonical transcriptional pathway orchestrated by TFEB adapts cells to stress in all kinds of tissues by supporting lysosomal and autophagosome biogenesis. However, emerging findings highlight that TFEB activates other genetic programs involved in cell proliferation, metabolism, inflammation and immunity. Here, we first summarize the general principles and mechanisms by which TFEB activates its transcriptional program. Then, we analyze the current knowledge of TFEB in the vascular system, placing particular emphasis on its regulatory role in angiogenesis and on the involvement of the vascular unit in inflammation and atherosclerosis.